Ultrafiltration Treatment For Spent Tungsten Slurry Generated By Chemical Polishing Process In Wafer Fabrication Industry For Reuse - Sanusi, Nur Fatin Amalina Muhammad (2017)
Chemical Mechanical Polishing (CMP) is a widely used process to planarize wafers for microelectronic applications. It involves the polishing of metallic surface by chemical action followed by the removal of the modified layer by mechanical action using tungsten slurry. It is a rather complex mixture that both physical and chemical properties of the components in the slurry are expected to change depending on the condition and type of treatments that they receive. As such, characterization of the spent tungsten slurry and knowledge on its physical and chemical properties are critical in order to consider suitable recovery methods. Recycling of the abrasive slurry is one of the options to reduce the manufacturing cost and to achieve environmental benefits that arise from the reduction of wastewater volume. Crossflow ultrafiltration system was used as a method to recycle the silica based slurry. It investigated using three membrane materials i.e. polysulfone (PS), polyethersulfone (PES) and polyvinylidene fluoride (PVDF) with different molecular weight cut off (MWCO) of 10, 30, 50 and 100KDa. Effects of transmembrane pressure (TMP) on flux flow rate were characterized. Analyses of selectivity, retention and pH adjustment of feed water were done to demonstrate the membrane performance and fouling phenomena. A TMP of 1 bar gave the lowest fouling result as compared to the other TMPs. The PS 50KDa membrane demonstrated the best results with 92% retention of silica particles and only 42% retention of tungsten. It also achieved the lowest mean size particle of 125nm in the retentate or only 0.5% value difference compared to that of the original spent tungsten slurry than those of other membranes especially PVDF membrane with the same MWCO. The performance in spent tungsten slurry recovery could be improved by adjusting the pH to 9 that gave the best performance in terms of having the lowest mean size of 126 nm which was close to 125 nm of the original size of particles in the spent tungsten slurry. It gave the highest retention of silica particles of 42% in the retentate. It also had the largest negative value of -40mV in zeta potential to suggest its stability. In conclusion, PS ultrafiltration with 50KDa of MWCO membrane showed the highest potential in filtrating and concentrating the spent tungsten slurry of CMP process with the best result achieved at a pH value of 9.